Secondary Use of Data: Non-Interventional Study Best Practices in Planning and Protocol Development - Juanzhi Fang; Sara Bruce Wirta; Kristijan Kahler (Journal of Health Economics and Outcomes Research)
Well established guidelines already exist that address best practices for Non-Interventional Study (NIS) design and methods. These guidelines provide advice on things to consider while designing a study and developing a protocol, but do not necessarily capture specific details related to the implementation of NIS. The intent of this paper is to propose a best practice for conducting secondary use of data NIS. We propose that the ideal implementation of a NIS should include the development of a strong Study Concept, followed by a detailed Protocol, Analysis Plan, Report, and considerations for Dissemination.